A parallel PDE-based numerical algorithm for computing the Optical Flow in hybrid systems - Cuomo, Salvatore; De Michele, Pasquale; Galletti, Ardelio; Marcellino, Livia (Journal of computational science, 2017)
•A fine-to-coarse parallelization strategy in order to exploit a parallel hybrid architecture is proposed.•We consider the Optical Flow numerical problem and implement a parallel multilevel software.•A hybrid software solution combining codes on Graphic Processor Units is proposed.•Numerical experiments highlight good results in terms of performance for the proposed approach. In this paper, we propose a fine-to-coarse parallelization strategy in order to exploit, in a case study, a parallel hybrid architecture. We consider the Optical Flow numerical problem, modelled by partial differential equations, and implement a parallel multilevel software. Our hybrid software solution is a smart combination between codes on Graphic Processor Units (GPUs) and standard scientific parallel computing libraries on a cluster. Numerical experiments, on real satellite image sequences coming from a large dataset in a big data scenario, together with application profiling, highlight good results in terms of performance for the proposed approach.